Investigating the costs of major and minor cycling crashes in Tasmania, Australia - Andrew J. Palmer; Lei Si; Jared M. Gordon; Tim Saul; Petr Otahal; Peta L. Hitchens (Elsevier, 2015)
Abstract Objective: A pilot study to estimate the societal costs of cycling crashes in Tasmania. Methods: A telephone‐based questionnaire collected information on demographics, cycling habits and details of major and minor crashes. Costs were estimated from medical resource consumption, lost work and leisure time. Results: The survey was completed by 136 cyclists. Participants reported 59 major crashes in five years preceding the interview and 27 minor crashes in 12 months. Mean (standard deviation) costs/major crash were $12,499 ($14,301), including direct medical costs $2,569 ($4,523), direct non‐medical costs $372 ($728), indirect costs of $6,027 ($10,092) and costs of lost leisure time $3,531 ($7,062). Costs/minor crashes were $632 ($795), including direct non‐medical costs of $225 ($601), productivity losses of $117 ($210) and costs of lost leisure time $290 (622). Total annual costs of major cycling crashes in Tasmania were $4,239,097 ($4,850,255). Conclusions: Indirect costs and costs due to lost leisure time are major contributors to the total societal costs. The comprehensive quantification of costs of crashes will inform decision makers formulating policies that improve the safety of cyclists leading to reductions in the economic burden on society.